Changing Trends (Patterns) of Human Poisoning in Kadapa Region – a Five Years Study - B. Nagendra Prasad; L. Anand Kumar (Institute of Medico-legal Publications Pvt Ltd, 2021)
“Caution is advised while decontaminating a victim of poisoning. Over enthusiasm may result in the patient, not the poison” – John Morrision Poisoning has been known to mankind since time immemorial and the study of various poisons and their effects has always fascinated mankind. References to poisons and various instances of poisoning are available in Indian Shastras, Egyptian Papyari and Sumerian writings.1Since then many substances considered advantages and disadvantages in the form of food or poisons have been discovered. Those substances which are used unfortunately to take away the man’s life or cause ill health have been changing. Some of the great persons who were poisoned to death are Chatrapati Shivaji Maharaj,2-3 whose bed was poisoned, Socrates, who was made to drink Hemlock (Conium maculatum) and Rasputin who was poisoned with cyanide and then shot. Aluminum phosphide poisoning, a rodenticide is also posing a formidable challenge and is on the way for taking the number one position. As poisoning trends go on changing, it is necessary to know the poisoning trends from time to time.